Information model of economy - Gonchar, N.S. (Condensed Matter Physics, 2006)
A new stochastic model of economy is developed that takes into account the choice of consumers are the dependent random fields. Axioms of such a model are formulated. The existence of random fields of consumer’s choice and decision making by firms are proved. New notions of conditionally independent random fields and random fields of evaluation of information by consumers are introduced. Using the above mentioned random fields the random fields of consumer choice and decision making by firms are constructed. The theory of economic equilibrium is developed.